Corydalis nanchuanensis (Papaveraceae), a new species from Chongqing, China - Zhang, Bu-Yun; Xiao, Jin-Fei; Yi, Si-Rong (Phytotaxa, 2021)
Corydalis nanchuanensis (Papaveraceae), a new species from Nanchuan district in south-west Chongqing, China, is described and illustrated. Morphologically, the new species is similar to C. sheareri, a species mainly distributed in south China and Vietnam, in having conical corolla spurs, divided lower bracts, rounded stigmas, larger elaiosomes (usually longer than seeds), and tubers, but differs by having tapering-to-base (vs. uniformly sized) stems; entire (vs. usually crenate) leaf lobes, straight (vs. declined) pedicels in fruit, concave (vs. subacute) apices of outer petals, white (vs. usually purple) abaxial side of inner petals, and reticulate (vs. tuberculate) seeds.